TEACHING ENGLISH GRAMMAR USING PROBLEM BASED LEARNING JO. WITH PUZZLE AT ENGLISH EDUCATION STUDENT OF IKIP SILIWANGI BANDUNG - Acep Haryudin; Trisnendri Syhrizal (IKIP Siliwangi, 2018)
The the purposes of this resaearch was to find out students dificulty in mastering Grammar, and to find out the suitable method in improving students’ grammar mastery. The method of this research was Action Research as the application of fact finding to practical problem solving in social situation by involving the collaboration and cooperation of researcher and practitioners. The research took place at IKIP Siliwangi, focused on class A2 year 2016. Subjects of the research was 45 students of English Education Study Program. The finding and disscussion of this research was that Problem Based Learning (PBL) jo with Puzzle media could improve students’ grmammar mastery and students of English Education Study Program could